Sistem Jaminan Halal: Studi Komparatif Indonesia dan Malaysia - Isti Nuzulul Atiah; Ahmad Fatoni (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2019)
Consumption of the halal product industry in Indonesia has great potential to be developed, because Indonesia is a Muslim-majority country. In recent years, the development of halal food consumption trends has increased significantly, not only in Muslim-majority countries but this is also experienced by Muslim minority countries. Halal food market demand encourages food producers to obtain halal certification from local authorities. This study aims to compare the mechanism and application of halal certification in Indonesia and Malaysia. This study uses a qualitative descriptive approach and the type of research used in this study is a literature study that collects information relevant to the research objectives. The conclusion of this study is that both Indonesia and Malaysia, both apply almost the same principles, authority and halal certification mechanism. One of them is for every producer who will propose halal certification, is required to go through a series of tests in which the test results will be submitted to the Fatwa Commission which is authorized to decide whether or not a product is halal.